Temporal and spatial regulation of mRNA export: Single particle RNA‐imaging provides new tools and insights. (4th January 2017) - Heinrich, Stephanie; Derrer, Carina Patrizia; Lari, Azra; Weis, Karsten; Montpetit, Ben
Abstract : The transport of messenger RNAs (mRNAs) from the nucleus to cytoplasm is an essential step in the gene expression program of all eukaryotes. Recent technological advances in the areas of RNA‐labeling, microscopy, and sequencing are leading to novel insights about mRNA biogenesis and export. This includes quantitative single molecule imaging (SMI) of RNA molecules in live cells, which is providing knowledge of the spatial and temporal dynamics of the export process. As this information becomes available, it leads to new questions, the reinterpretation of previous findings, and revised models of mRNA export. In this review, we will briefly highlight some of these recent findings and discuss how live cell SMI approaches may be used to further our current understanding of mRNA export and gene expression. Abstract : mRNA export is fundamental to eukaryotes, yet it remains to be understood how this process is regulated in space and time to facilitate gene expression. This review highlights developments in quantitative single molecule imaging (SMI) of RNA in vivo and discusses key questions that can be addressed with SMI.